Venetoclax in Acute Myeloid Leukemia: Molecular Basis, Evidences for Preclinical and Clinical Efficacy and Strategies to Target Resistance - Sylvain Garciaz (MDPI AG, 2021)
Venetoclax is a BH3-mimetics agent specifically interacting with the antiapoptotic protein BCL-2, facilitating cytochrome c release from mitochondria, subsequent caspases activation, and cell death. Utilization of venetoclax has profoundly changed the landscape of treatment for the poor-prognosis category of AML patients unfit for intensive chemotherapy. In the phase III VIALE-A study, Venetoclax, in combination with the hypomethylating agent azacitidine, showed a 65% overall response rate and 14.7-month overall survival, in comparison with 22% and 8 months in the control arm. These results led to the widespread use of venetoclax in this indication. Other combination regimens, consisting of low-intensity, intensive, or targeted therapies are currently under evaluation. Despite promising results, preventing relapses or resistance to venetoclax is still an unmet clinical need. Numerous studies have been conducted to identify and overcome venetoclax resistance in preclinical models or in clinical trials, including the inhibition of other antiapoptotic proteins, the induction of proapoptotic BH3-only proteins, and/or the targeting of the mitochondrial metabolism and machinery.